Near Surface Carbon Dioxide and Methane in Urban Areas of Costa Rica - Esquivel-Hernández, Germain (2015)
Little information is available for Central America regarding methane and carbon dioxide mixing ratios in urban areas. This work reports a representative spatial and seasonal study of near surface carbon dioxide and methane, carried out between July 2014 and January 2015 (27 weeks) in the Central Valley of Costa Rica, and other urban and rural sites across the country and covering three distinct seasons: Mid-summer drought (July-August), wet season (September-November) and transition period (December-January). The mixing ratios of both gases are clearly influenced by the metropolitan area, and by the prevailing atmospheric conditions during the wet season months. Average carbon dioxide concentration (629 ± 80 ppm) and average methane concentration (2192 ± 110 ppb) were up to 8% and up to 10%, respectively, higher during the wet season than the values recorded outside this period. HYSPLIT back air mass trajectories analysis, and weather data available for the Central Valley, suggest that these differences arise as result of a reduction in the mixing layer of depth (~425 m) and the wind speed (~1.5 m/s) across the valley, favoring the accumulation of polluted air masses in the metropolitan area. Other natural and anthropogenic sources, like the volcanic emissions of the Turrialba Volcano and the livestock activities at rural sites, apparently influence the mixing ratios of both gases across Costa Rica. Although the scope of this study is limited to representative seasonal conditions of the Central Valley in 2014 and 2015, it is possible considering the information presented in this work that the “dome” phenomenon can be assumed to exist.